Description of Laboratory Examination Results of Systemic Lupus Erythematosus (SLE) Patients Based on Mex-SLEDAI Levels at Raden Mattaher Hospital Jambi - Syafawani Musfirah; Imanuel Sitepu; Patrick William Gading; Sotianingsih .; Nyimas Natasha Ayu Shafira (CV. ITTC INDONESIA, 2026)
Background: Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease with diverse clinical manifestations involving multiple organs. Disease activity reflects the severity of SLE and can be assessed using the Mexican Systemic Lupus Erythematosus Disease Activity Index (Mex-SLEDAI). Laboratory parameters play an important role as indicators in evaluating disease activity. Objective: To describe laboratory examination findings based on Mex-SLEDAI disease activity levels in SLE patients at Raden Mattaher Hospital Jambi. Methods: This study used a descriptive retrospective design based on medical records of SLE patients at Raden Mattaher Hospital, Jambi, from 2021 to August 2025. Total sampling was applied, and 29 samples were included. Results: Most patients were female (93.1%) and aged 25–44 years (69.0%). The majority had mild disease activity based on Mex-SLEDAI (48.3%). Anemia was most frequently found in mild activity (44.8%). Leukocytopenia and thrombocytopenia were more commonly observed in moderate activity (10.3% each). Proteinuria (13.8%) was more frequent in severe activity, while hematuria (17.2%) was most commonly found in moderate activity. Conclusion: Most SLE patients were female, aged 25–44 years, with predominantly mild disease activity. Renal parameters such as proteinuria and hematuria tend to appear at higher disease activity levels, whereas hematological parameters do not show a consistent pattern.